Pronunciation Of The English Voiceless Postalveolar Affricate /tʃ/ In Yemeni EFL Learners’ Production - Najah Ahmad Khamis; Rohaiza Jupri (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
Achieving a near-native speaker’s pronunciation is so essential for EFL learners. However, many factors contribute to the challenges faced by EFL learners, mainly due to the difference in the sound system of English Language and that of their first language. For this reason, Arab learners of English Language may mispronounce some English sounds. This paper analyzed one of the few problematic sounds to the Arab Yemeni EFL learners - the pronunciation of the English voiceless postalveolar affricate /ʧ/. The study which has a quantitative case study design uses four Yemeni EFL postgraduate students as its participants. The participants’ pronunciations of /tʃ/ sound in the initial, middle and final word-positions were analyzed using Praat phonetic software. The findings of the study showed that Yemeni EFL learners have difficulties in producing the /tʃ/ sound, especially in the initial and final positions, and deaffrication of /tʃ/  occurred in the  pronunciation of the four participants. The current study is expected to be of value, particularly for EFL learners, teachers, as well as material writers.